Intervention in the historical monuments of the Center of Lima: An analysis of the methodology applied in the Adopt a Balcony campaign - Copaira Ortiz, María (2018)
The Historic Center of Lima is one of the main elements of the city’s identity, which is why its sustainability and revitalization should be given special attention. Nevertheless, for a long time it has been buried in oblivion, subsisting in a state of total abandonment that has led to its gradual degradation. However, in recent years multiple interventions in the buildings in that area have taken place, all aiming to safeguard them. On the other hand, some of those interventions have actually endangered the building’s authenticity, because the planning and “criteria” employed in developing the project are based on different theoretical concepts resulting from the interpretations of various theories of intervention and numerous letters of patrimonial preservation. It is vital to reflect on the consequences of the application of the interpretations given to this theories and letters, because that will allow the analysis of intervention processes in order to establish recommendations and suggest criteria that will improve the management of these processes and incorporate the use of patrimonial management models. So, here an intervention methodology is raised and analyzed using as an example the specific case of the Adopt a Balcony campaign, undertaken by the Metropolitan Municipality of Lima between 1997 and 2002.